PLOT ANALYSIS IN CHARLES DICKENS’ GREAT EXPECTATIONS - Arif Dwi Cahyono; Lailatul Musyarofah; Eka Fadilah (Linguistics and Literature Students' Journal, 2023)
This research examines about plot analysis in Charles Dickens’ Great Expectations. The purpose of this research was to plots by Charles Dickens’. Great Expectations novel 1861 by Charles Dickens’ that the novel work of literature Victorian era. Dickens’ novels belong decidedly to the class of purposes or problem novels. He wished to make the novel an instrument of morality and justice, and his stories did more to correct the general selfishness and injustice of society towards the poor than all the works of other literary men of his age combine. This research using of plot theory. The authors can give the readers a deeper understanding of what the plot process idea in Charles Dickens’ Great Expectations. The plot in Charles Dickens’ Great Expectations the author find that Dickens arranges the story by using chronological order. Having analyzed point of view the author finding out that in telling the events of the story. The author uses the first person of view, first person narrators are usually identified and differentiated on the basis of their degree of involvement with the events of the plot. Thus, the point of view in Great Expectations is given partly to the readers to judge the story by themselves. Keywords: Plot, Literature, Point of View, Novel, Great Expectations